Penyuluhan dan Pelatihan Membuat Media Pembelajaran Animasi Flash Kepada Guru-guru Sekolah Dasar di Kelurahan Bakaran Batu - Fitria, Eva; Indra, Aulia (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2023)
Animation comes from the Latin word "anima" which means soul, life, spirit. Meanwhile, characters are people, animals and other real objects that are presented in the form of 2D and 3D images. So that animated characters can be interpreted as images containing objects that appear to be alive, caused by the collection of images changing regularly and alternately being displayed. Objects in images can be text, shapes, colors and special effects. The purpose of this community service is to improve the learning system and methods in learning. So that students do not feel bored in class. The result of the counseling is that the participants/teachers are able to make flash animations with this counseling and training and the participants are able to improve applying the flash animation learning method in class